2010
DOI: 10.1111/j.1439-0434.2009.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Tatumella ptyseos, an Unrevealed Causative Agent of Pink Disease in Pineapple

Abstract: Pink disease is a major problem in the pineapple canning industry. Affected fruit acquire a brownish pigment after pasteurization and can contaminate non-affected fruit before they are released to the consumer. In the last few years, Pantoea citrea has been described as the causative agent of pink disease. In this study, over 300 bacterial isolates from pineapple plants, growing in Mexican commercial fields, and from soil close to plant roots were recovered. Over 250 isolates showed a very high similarity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Tatumella is an Enterobacteriaceae that has been linked to both human and plant infections (Costa, Mendes & Ribeiro, 2008; Marin-Cevada et al, 2010). Tatumella punctata, the nearest hit to the largest Tatumella OTU identified in this study, was originally isolated from oranges (Kageyama et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Tatumella is an Enterobacteriaceae that has been linked to both human and plant infections (Costa, Mendes & Ribeiro, 2008; Marin-Cevada et al, 2010). Tatumella punctata, the nearest hit to the largest Tatumella OTU identified in this study, was originally isolated from oranges (Kageyama et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Pineapples are subject to a variety of diseases, which include wilt disease, pink disease, bacterial heart rot, anthracnose, fungal heart rot, root rot, black rot, butt rot, fruit let core rot, and yellow spot virus [7,11]. Contamination of pine apples may take place at all stages during pre and post-harvest stages.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical isolates of Tatumella ptyseos , a member of the family Enterobacteriaceae , are primarily obtained from patient sputa (Berkta et al , 2001; Hollis et al , 1981; Tan et al , 1989), and members of the genus Tatumella have been isolated previously from food and environmental samples (Brady et al , 2010; Garcia-Armisen et al , 2010; Ken et al , 2005; Marín-Cevada et al , 2010; Papalexandratou et al , 2011b). Phylogenetic studies using 16S rRNA gene sequence analysis suggest that T. ptyseos is closely related to bacteria of the genus Erwinia (Drancourt et al , 2001; Spröer et al , 1999), and comparative genetic analyses have demonstrated that T. ptyseos is also related to Morganella morganii and the genus Pantoea (Paradis et al , 2005; Brady et al , 2010).…”
mentioning
confidence: 99%
“…Pairwise sequence alignments (shown in Table S2) were made between NML 06-3099 T and species reassigned to the genus Tatumella in 2010 (Brady et al , 2010), including (identity to the type strain): T. citrea (98.3 %), T. morbirosei (97.9 %), T. punctata (98.6 %) and T. terrea (98.7 %). Notably, the 16S rRNA gene sequence for NML 06-3099 T has been detected in separate sources of fruit in independent studies, including cocoa beans from Ecuador (Papalexandratou et al , 2011a) and Malaysia (Papalexandratou et al , 2013), pineapples from Mexico (Marín-Cevada et al , 2010) and a garden microbiome in Panama (GenBank accession no. HM556908).…”
mentioning
confidence: 99%
See 1 more Smart Citation